X-ray photoelectron spectroscopy as a probe of rhodium-ligand interaction in ionic liquids - Men, Shuan; Lovelock, Kevin; Licence, Peter (Elsevier, 2016)
We use X-ray photoelectron spectroscopy (XPS) to identify the interaction between the rhodium atom and phosphine ligands in six 1-octyl-3-methylimidazolium-based ionic liquids ([C8C1Im][X]). The formation of a mono-phosphine rhodium complex based upon addition of triphenylphosphine (PPh3) is confirmed by XPS in all ionic liquids studied herein. Due to the electron donation effect of the ligand, the rhodium atom becomes more negatively charged and thus exhibits a lower measured binding energy. The influence of the anion basicity on the formation of different types of rhodium complexes is also investigated. By introducing a biphosphine ligand, a chelated diphosphine rhodium complex is formed in ionic liquids with more basic anions and verified by both XPS and Infrared Spectroscopy (IR). The measured Rh 3d binding energies are correlated to the reaction selectivity of a hydroformylation reaction which inspires a method to design a metal catalyst to control the chemical reaction towards desired products in the future.